PRODUCTIVITY AND ANALYSIS OF FEASIBILITY ANALYSIS OF KELONG EQUIPMENT IN MALANG RAPAT VILLAGE GUNUNG KIJANG DISTRICT BINTAN REGENCY RIAU ISLAND PROVINCE - Evriliyana Dwi Putri Br Surbakti; Pareng Rengi; Bustari Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACKThis research was conducted in April 2018, in Malang Rapat Village of Gunung Kijang District, Bintan Regency, Riau Island Province. The purpose of this study was to determine the composition of species of catch and productivity of kelong fishing gear during the study. As well as to find out how feasibility of kelong fisheries business in Malang Rapat Village. The method used is survey.The composition of the catch of kelong is anchovy, squid, and tamban fish. The highest productivity occurs in kelong 2 on day 3 of 0,173 kg/minute and the lowest occurs in kelong 3 on day 8 0f 0,04 kg/minute. In running a fishing business using kelong fishing gear the cost incurred are quite large, which is Rp. 158.900.000,-. For initial capital and fishing business using kelong is still considered profitable because it has been analyzed using BCR, FRR, and PPC with a capital return of 2,3 years where the economic life of the fishing gear is 5 years. Keyword : Productivity, Composition, Business Feasibility, Kelong Fishing Gear